Preoperative stabilisation in congenital diaphragmatic hernia. - Shanbhogue, L K (1990)
Between January 1983 and November 1986, 26 newborn infants with congenital diaphragmatic hernia were treated by early operation at a mean of 7 hours of age. A further 23 infants admitted between December 1986 and December 1989 were stabilised for a mean period of 40 hours before operation. There was no significant difference in survival between the two groups. Delayed operation is not detrimental to infants with congenital diaphragmatic hernia.